Liver Transplantation for Propionic Acidemia and Methylmalonic Acidemia: Perioperative Management and Clinical Outcomes. Issue 9 (24th September 2018) - Critelli, Kristen; McKiernan, Patrick; Vockley, Jerry; Mazariegos, George; Squires, Robert H.; Soltys, Kyle; Squires, James E.
Abstract: Propionic acidemia (PA) and methylmalonic acidemia (MMA) comprise the most common organic acidemias and account for profound morbidity in affected individuals. Although liver transplantation (LT) has emerged as a bulk enzyme‐replacement strategy to stabilize metabolically fragile patients, it is not a metabolic cure because patients remain at risk for disease‐related complications. We retrospectively studied LT and/or liver‐kidney transplant in 9 patients with PA or MMA with additional focus on the optimization of metabolic control and management in the perioperative period. Metabolic crises were common before transplant. By implementing a strategy of carbohydrate minimization with gradual but early lipid and protein introduction, lactate levels significantly improved over the perioperative period ( P < 0.001). Posttransplant metabolic improvement is demonstrated by improvements in serum glycine levels (for PA; P < 0.001 × 10 –14 ), methylmalonic acid levels (for MMA; P < 0.001), and ammonia levels (for PA and MMA; P < 0.001). Dietary restriction remained after transplant. However, no further metabolic crises have occurred. Other disease‐specific comorbidities such as renal dysfunction and cardiomyopathy stabilized and improved. In conclusion, transplant can provide a strategy for altering the natural history of PA and MMA providing stability to a rare but metabolically brittle population. Nutritional management is critical to optimize patient outcomes.